Design of New Energy-Absorbing Lattice Cell Configuration by Dynamic Topology Optimization - Yongxin Li; Qinghua Li; Xingxing He; Shenshan Li; Yongle Wang (Metals)
In this study, we focus on the new energy-absorbing lattice cell configuration designed by topology optimization. To address the difficulty involved in the quantitative description of densification in periodic lattice plastic deformation, in this study, we propose characterizing the plastic densification state of a porous structure with the maximum ratio of two adjacent equivalent plastic moduli in the nonlinear static analysis process. Then, dynamic topology optimization is carried out with the maximization of the absorbed energy as the objective and the densification strain as the constraint to obtain the new topological configuration of the energy-absorbing lattice cell. Finally, additive manufacturing and quasistatic testing of the new energy-absorbing lattice structure and body-centered cubic and face-centered cubic lattice structure is conducted. The results show that, under the same conditions, the strain energy absorbed by the energy-absorbing lattice is approximately 3.5 times that absorbed by the body-centered cubic structure and 2.8 times that absorbed by the face-centered lattice structure with a low impact speed of 5 m/s.